Congenital pouch colon with ileovesical and colovesical fistulae: A new variant - Bilal Mirza; Lubna Ijaz; Maham Zaman; Afzal Sheikh (Wolters Kluwer Medknow Publications, 2011)
We report a case of persistent cloaca and type I congenital pouch colon associated with ileovesical and colovesical fistulae. Such a malformation has not been reported so far.